Interpolation of discount factors - Heinz Cremers; Willi Schwarz (Hochschule für Bankwirtschaft (HfB), 1996)
This paper deals with the problem of interpolation of discount factors between time buckets. The problem occurs when price and interest rate data of a market segment are assigned to discrete time buckets. A simple criterion is developed in order to identify arbitrage-free robust interpolation methods. Methods closely examined include linear, exponential and weighted exponential interpolation. Weighted exponential interpolation, a method still preferred by some banks and also offered by commercial software vendors, creates several problems and therefore makes simple exponential interpolation a more logical choice. Linear interpolation provides a good approximation of exponential interpolation for a sufficiently dense time grid.
urn:nbn:de:101:1-2008070285
Keywords: 330